Search for sorority – in the color purple: - (Journal of Advances and Scholarly Researches in Allied Education, 2022)
“Don’t wait around for other people to be happy for you, And happiness you get you’ve got tomake yourself” (Alice Walker) This study explains that women bonding or sorority can help women to gethappiness. If they want to raise themselves from their oppressed condition, they must come together.They should not wait for men to come and help them. Women sorority or bonding only can liberate themand make them comfortable in male dominated society. It is with Shug that Celie first consummates asatisfying and reciprocally loving relationship. It is the support of Shug that Celie becomes anindependent woman at peace with herself, able to combat the conditions that oppressed her, made her“wood”.